Breadth of University Curriculum and Labor Market Outcomes - Kelvin Seah; Jessica Pan; Poh Lin Tan (Institute of Labor Economics (IZA), 2020)
We explore whether the choice of broad versus specialized university curricula affects subsequent labor market outcomes, as measured by earnings, full-time permanent employment, and unemployment six months after university graduation. We exploit a unique episode in the history of the National University of Singapore, in which a university-wide revision in graduation requirements in 2007 prompted students in one of the largest faculties to read a narrower, more specialized, curriculum. Using a difference-in-differences strategy, we compare changes in the labor market outcomes of graduate cohorts from the affected faculty, before-and-after the curriculum revision, to changes in the labor market outcomes of graduate cohorts from the other faculties. We do not find evidence that curriculum breadth matters for these labor market outcomes. Similar conclusions are obtained using regression-control strategies and rich administrative data on student characteristics and academic ability for the broader population of undergraduates at NUS.
Keywords: I21; J31; 330; university curriculum; curriculum breadth; difference-in-differences; earnings; employment